Creation of Attractive Digital Marketing to Improve the Branding of Pematang Johor Community Businesses - Rahmad Dianta Purba; Linda Wahyu Marpaung; Muhammad Hafiz Abd.Rashid; ⁠Hendra Halim; Sipnarong Kanchawongpaisan; Phan Bao Giang; Nabila Dwi Puspita Sari (Eastasouth Institute, 2025)
This community service and research project aims to enhance the digital capabilities of the Pematang Johar Rice Field Tourism Village community through strengthened branding and digital marketing. The activity was motivated by the significant decline in tourist visits during the COVID-19 pandemic, which highlighted the need for more adaptive promotional strategies. The study employed a descriptive-participatory approach consisting of observation, socialization, training, and mentoring activities. A total of 60 participants were involved in training sessions covering visual content production, social media management, Google Maps optimization, and village website development. Pre-test results indicated low levels of digital literacy (40/100), while post-test scores increased sharply to 90/100 after the mentoring sessions. Beyond technical improvements, the program also led to social transformation, including the formation of a village digital team, increased collaboration among MSMEs, and the establishment of a new branding identity: “Pematang Johar – Rice Field Tourism on the Outskirts of Medan City.” The outcomes demonstrate that digital marketing is an effective strategy for promoting tourist villages and supporting sustainable local economic growth.